Social Inclusivity as a Pillar of Cultural Resilience in the Kejawen Community in Central Java, Indonesia - Dadan, Sulyana; Nazila, Saufa Rohmatun; Suksmadi, Ignatius; ., Chusmeru (Journal of Cultural Analysis and Social Change, 2026)
The Kejawen community is an ancient religion in Indonesia. Despite being influenced by the modern world, the Kejawen Community has firmly maintained its cultural identity. This research explores how the cultural resilience strategy carried out by the Kejawen Community maintains its culture amid the dynamics of global life. This study used a qualitative method. The research informants were the Chairman and members of the Kejawen Community, village officials, and the society. The data were collected through in-depth interviews and observations. Data analysis uses interactive analysis. This study found that the cultural resilience strategy of the Kejawen Community was social inclusivity. Social inclusivity is carried out both inward and outward. Inclusivity is carried out by involving non-Kejawen people in various rituals that they conduct regularly. Meanwhile, inclusivity to the outside is conducted by actively participating in various activities organized by society, government, and other cultures.